Teachers’ Perspectives on the Ideology of Native-Speakerism: A Case Study in West Jakarta - Maria, Marcella Sonya; Kurniawati, Farida Nova; Putri, Rizky Syahra (JELLT (Journal of English Language and Language Teaching), 2025)
This study explores the perspectives of primary school English teachers in West Jakarta on native-speakerism and its impact on their teaching experiences. Native-speakerism, the belief that native speakers from Inner Circle countries are superior in language proficiency and teaching ability, continues to influence educational practices worldwide. The research investigates how this ideology shapes teachers' opinions on the value of foreign teachers, their reactions to native-speakerism in the classroom, and their personal experiences with this dominant teaching paradigm. Data were collected through semi-structured interviews with three English teachers from National Plus Schools. Findings reveal that while teachers acknowledge the perceived advantages of native speakers, such as superior pronunciation and authoritative teaching materials, they also challenge the notion that nationality is a determining factor for teaching effectiveness. Teachers emphasized the importance of proficiency and motivation over nationality and accent, suggesting a more inclusive approach to language teaching. The study contributes to the growing body of literature critiquing the native-speakerism ideology and advocates for a more equitable and diverse perspective on English language teaching. Future research could examine the implications of native-speakerism at various educational levels and its influence on teacher identity and hiring practices.